Four Methods for Defining Organizational Boundaries in Sociology - ЧириковИгорь Сергеевич (Journal of Economic Sociology, 2012)
The paper codifies the theoretical perspectives in sociology of organizations related to studies in organizational boundaries. Four methods for conceptualizing organizational boundaries are identified, depending on a key metaphor which each method proposes. The presented metaphors include (1) boundary as membrane (flap); (2) boundary as convention; (3) boundary as interface; (4) boundary as forefront. In addition, the paper discusses the organizational perspectives’ general methodological drawbacks in studying organizational boundaries.